Community-based point-of-care testing to identify new HIV infections: A cross-sectional study from Pune, India. Issue 46 (19th November 2021) - Mamulwar, Megha; Prasad, V. Sam; Nirmalkar, Amit; Goli, Sarita; Jadhav, Sachin; Kumbhar, Shamali; Kale, Varsha; Michael, Elizabeth; Ford, Teresa Marie; Nazarov, Denys; Honig, Lyle; Gangakhedkar, Raman; et al.
Abstract : Abstract: The World Health Organization recommends point-of-care testing (POCT) to detect human immunodeficiency virus (HIV) infected individuals in the community. This will help improve treatment coverage through detection of HIV infection among those who are unaware of their status. This study was planned with an objective to investigate the feasibility and acceptability of POCT for HIV in the community. A community-based cross-sectional study was conducted in rural and peri-urban areas of Pune, India. These sites were selected based on the distance from the nearest HIV testing center. Testing locations were identified in consultation with the local stakeholders and grass-root health workers to identify and capture the priority population. The POCT was performed on blood samples collected by the finger-prick method. The proportion of participants seeking HIV tests for the first time was 79.6% that signifies the feasibility of POCT. The acceptability in the peri-urban and rural areas was 70.2% and 69.7%, respectively. POCT was performed at construction sites (24.9%), nearby industries (16.1%) and parking areas of long-distance trucks (8.1%) in the peri-urban area. Three newly diagnosed HIV-infected participants (0.1%) were detected from the peri-urban areas but none from the rural areas. Two of the newly diagnosed participants and their spouses were linked to care. There was a high acceptability of POCT and wider coverage of priority population with a strategy of testing at places preferable to the study population. Therefore, we believe that community-based POCT is a promising tool for improving HIV testing coverage even in low prevalence settings with the concentrated HIV epidemic.